Internalisasi Islam Moderat dalam Upaya Peningkatan Literasi Moderasi Guru di Sekolah Kejuruan Kawasan Perbatasan - Sari, Nove Kurniati; Muhja, Zainal Abidin; Banyuriatiga (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2024)
The significance of the moderate Islam internalization approach within the educational context of border regions underscores the relevance and importance of this research endeavor. By focusing on the pivotal role of educators as primary agents, it becomes imperative to formulate effective strategies aimed at enhancing the literacy of moderate Islamic principles as an integral facet of personal and societal development within vocational school environments. The purpose of this study is to examine the efficacy of literacy-based instructional methods in promoting and cultivating religious moderation among educators in vocational schools situated within border regions. The research employs a quasi-experimental methodology with a primary emphasis on assessing the impact of literacy-oriented instruction on the comprehension of the significance of practicing religion moderately. This study also investigates the development of attitudes and behaviors characterized by religious moderation, as well as the fostering of sincere ethics and friendships among adherents of diverse faiths. The research findings indicate a positive effect of the literacy-based instructional approach on the predefined objectives. Educators who participated in this instructional approach demonstrated an improved understanding of the importance of practicing religion moderately. Moreover, they exhibited an enhanced ability to cultivate attitudes and behaviors characterized by religious moderation in their daily lives. The interaction between educators and practitioners of different faiths also exhibited greater harmony, thereby fostering an enhanced ethical framework for religious practice.